Obeticholic acid and 5β-cholanic acid 3 exhibit anti-tumor effects on liver cancer through CXCL16/CXCR6 pathway - Gou, Haoxian; Liu, Shenglu; Liu, Linxin; Luo, Ming; Qin, Shu; He, Kai; Yang, Xiaoli (Frontiers in Immunology, 2022)
Hepatocellular carcinoma (HCC) is the most common type of liver malignancy with a high incidence and mortality rate. Previous in vitro and in vivo studies have confirmed that liver sinusoidal endothelial cells (LSEC) secrete CXCL16, which acts as a messenger to increase the hepatic accumulation of CXCR6+ natural killer T (NKT) cells and exert potent antitumor effects. However, evidence for this process in humans is lacking and its clinical significance is still unclear. In this study, by dissecting the human HCC single-cell RNA-seq data, we verified this process through cellphoneDB. NKT cells in patients with high expression of CXCL16 exhibited a higher activation state and produced more interferon-γ (IFN-γ) compared with those with low expression. We next investigated the signaling pathways between activated (CD69 high) and unactivated NKT cells (CD69 low) using NKT cell-developmental trajectories and functional enrichment analyses. In vivo experiments, we found that farnesoid X receptor agonist (obeticholic acid) combined with the takeda G protein coupled receptor 5 antagonist (5β-cholanic acid 3) exhibited significant tumor suppressive effects in the orthotopic liver tumor model and this result may be related to the CXCL16/CXCR6 axis. In conclusion, our study provides the basis and potential strategies for HCC immunotherapy based on NKT cells.